2008
DOI: 10.1159/000117715
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Histone Isoforms on the Bovine Active and Inactive X Chromosomes

Abstract: The inactive X chromosome (Xi) in female mammals serves as an important model for studying the role of histone isoforms in directing specific nuclear processes leading to inherited differences in transcription. In the present study, we investigated the distribution of some histone isoforms known to be involved in the process of human X inactivation on their bovine counterparts. To ascertain the identity of active and inactive X chromosome, their distribution was investigated on the X chromosomes in a cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 103 publications
3
18
0
Order By: Relevance
“…However, Chadwick and Willard (6) described an enrichment of these modified histones on human Xi and noted that they are spatially distributed in regions that are nonoverlapping with regions of elevated H3K27me3. Also, in bovine models, H3K27me3 and H3K9me3 are spatially distributed in nonoverlapping regions (7). This observed pattern of the mutually exclusive presence of H3K27me3 and H3K9me3 supports our findings in the mouse and possum that although H3K27 has an enhanced presence on the mouse Xi, it is not such a clear XCI mark in the possum.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, Chadwick and Willard (6) described an enrichment of these modified histones on human Xi and noted that they are spatially distributed in regions that are nonoverlapping with regions of elevated H3K27me3. Also, in bovine models, H3K27me3 and H3K9me3 are spatially distributed in nonoverlapping regions (7). This observed pattern of the mutually exclusive presence of H3K27me3 and H3K9me3 supports our findings in the mouse and possum that although H3K27 has an enhanced presence on the mouse Xi, it is not such a clear XCI mark in the possum.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, Xi chromatin is enriched in the histone variants macroH2A1 and macroH2A2 (5). In human and bovine models, H3K27me3 and H3K9me3 are spatially distributed in nonoverlapping regions (6,7). These stable histone modifications appear shortly after the accumulation of Xist RNA along the X with H3K9 methylation as the first modification occurring at the onset of XCI (8,9).…”
mentioning
confidence: 99%
“…4a). The bovine Xi chromosome displays two intense H3K27me3-rich bands at metaphase [55]. During interphase, a bright, heavily labeled patch was visible in the nucleus (Fig.…”
mentioning
confidence: 94%
“…Taking advantage of the morphological mark provided by this translocation to distinguish inactive from active X chromosome, an examination was carried out on the spatial distribution of a variety of histone isoforms including the histone H3, trimethylated at lysine-9 (H3K9me3) and at lysine-27 (H3K27me3), and two macro histones (macroH2A1 and macroH2A2). Comparison of the active and inactivated Xs in normal and translocation carrier bovine immunostained cells revealed that the histone variants H3K9me3, H3K27me3 and macroH2A1 are preferentially concentrated and consistently located in bands on the inactivated X in both types of bovine cells, as described for the human X chromosome (Brinkman et al, 2006) whereas H3K27me3 was identified in two intense bands on the inactivated X, at Xp22 and Xq31, representing the early replication regions of the X chromosome (Coppola et al, 2008). H3K27me3 and macroH2A1 overlapped in the Xq31 region, while macroH2A1 and macro-H2A2 were localized in the pericentric regions of all bovine autosomes.…”
Section: Heterochromatin Epigenetics and Chromatin Re-modelingmentioning
confidence: 63%